Glosa do wyroku Naczelnego Sądu Administracyjnego z 15 czerwca 2020 r., sygn. I OSK 2233/19 - Gacek, Paweł (Studia Prawa Publicznego, 2022)
The judgment commented on here concerned the issue connected with the period for filing an appeal. The view was shared that the period for lodging an appeal begins on the day on which the administrative decision is served upon the party (com- municated orally to the party) and it is at this moment that the period commences, although the day on which an administrative decision is served is not counted when calculating this time limit. Therefore, on the very day on which an adminis- trative decision is served, the party may submit an appeal against it, an application to reconsider the matter or waive the right of appeal. An appeal, an application to reconsider the matter or a statement on waiving the right of appeal are legally effective, because they are submitted during period for the filing an appeal. not content of Art. 57 (1) of The Code of Administrative Proceedings, which regulates the way of calculating the time limit in days. Given the content of this provision, it cannot be assumed that the period for lodging an appeal commences on the day following the one on which the administrative decision is served.